Desenvolvimento de sistema de informação geográfica para mapeamento da qualidade de maçã - Longo, Diego Rodrigo (2017)
The growing need for food, water scarcity, the biggest concern for the environment and the search for increased profitability are factors that have stimulated the adoption of precision agriculture. In this context appear new technologies as systems geared to support the decision-making. This paper presents a tool to map the apple quality indices georeferenced and turn them into a graphics variable to provide support in the orchard management. The system was developed in Java language, using the JavaServer Faces specification and the PrimeFaces graphics library. The database chosen to store the information was PostgreSQL with the geographical extension PostGIS. The result of this project was named Apple Show and has the ability to map the analyzed areas, mark the classified points and interpolate them, presenting them and classifying them in the form of maps.